In silico and in vitro testing Ascorbic Acid Protects Nicotine-Treated Human Erythrocytes - Panda, Pratikeswar; Sahu, Arpita; Mohapatra, Sagarika (Asian Journal of Pharmaceutical Research and Development, 2023)
Objectives: Nicotine is a naturally occurring drug that is highly addictive and is commonly found in tobacco products. Tobacco products are one of the leading causes of lung and oral cancer worldwide. Because blood is the primary organ in contact with nicotine, our goal in this study was to confirm its effect on blood. We also investigated the protective role of ascorbic acid on nicotine toxicity. Methods: Various blood toxicity studies were carried out using in-vitro and in-silico methods. Nicotine-induced haematological perturbation resulted in haemolysis, decreased superoxide dismutase and catalase activities, and decreased total antioxidant capacity in erythrocytes. Results and Conclusions: The results showed that nicotine has a negative effect on red blood cells in the lysis assay and causes clots to form in nicotine-treated samples in the blood clotting analysis. Furthermore, the in-Silico method validated the in-vitro results. According to our findings, ascorbic acid has blood-protective properties. Ascorbic acid was discovered to increase SOD, catalase, and total antioxidant activity. Ascorbic acid also reduced the damage caused by nicotine to RBCs in the lysis assay and demonstrated a high level of protection against the formation of clots when the samples were treated with nicotine. The findings suggest that ascorbic acid, an antioxidant, can protect against nicotine-induced haematological damage.